2019
DOI: 10.1177/0032321719852254
|View full text |Cite
|
Sign up to set email alerts
|

Emanating Effects: The Impact of the Oregon Citizens’ Initiative Review on Voters’ Political Efficacy

Abstract: Deliberative processes can alter participants’ attitudes and behavior, but deliberative minipublics connected to macro-level discourse may also influence the attitudes of non-participants. We theorize that changes in political efficacy occur when non-participants become aware of a minipublic and utilize its deliberative outputs in their decision making during an election. Statewide survey data on the 2010 and 2012 Oregon Citizens’ Initiative Reviews tested the link between awareness and use of the Citizens’ In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 54 publications
3
49
0
Order By: Relevance
“…To be of practical benefit for polities, minipublics must have impacts on the wider citizenry (Knobloch et al 2019: 2). In the absence of this impact, minipublics are faced with the challenges of scalability (Chambers 2009).…”
Section: The Effect Of Minipublics On Public Attitudesmentioning
confidence: 99%
See 1 more Smart Citation
“…To be of practical benefit for polities, minipublics must have impacts on the wider citizenry (Knobloch et al 2019: 2). In the absence of this impact, minipublics are faced with the challenges of scalability (Chambers 2009).…”
Section: The Effect Of Minipublics On Public Attitudesmentioning
confidence: 99%
“…Prior research has studied how minipublics affect deliberating individuals’ values and attitudes by boosting the coherence of their policy attitudes, democratic legitimacy beliefs, political efficacy, complexity of thinking, the quality of political knowledge and judgements (Fishkin 2009; Grönlund et al 2010; Himmelroos and Christensen 2014; Jennstål 2019; Lindell et al 2017; Luskin et al 2002; Muradova 2020; Suiter et al 2016b). More recently, attention has turned to whether such effects scale to the wider citizenry (Boulianne 2018; Felicetti et al 2016; Ingham and Levin 2018; Knobloch et al 2019).…”
mentioning
confidence: 99%
“…Reading the CIR statement seems to help voters make better informed and reflected decisions on ballot initiatives. A recent study by Knobloch et al (2019) finds that reading the CIR statement increases voters' political self-confidence, especially initiative-related efficacy. Moreover, the CIR seems actually facilitate critical judgement.…”
Section: The Cir As a Trusted Source Of Informationmentioning
confidence: 99%
“…The aim of the jury is to provide reliable and relevant information in order to help voters make decisions on ballot initiatives. Previous studies (see, e.g., Már & Gastil, 2020;Knobloch, Barthel, & Gastil, 2019) have shown that a CIR offers some remedies to problems of popular votes by enhancing voters' knowledge and capacity of judgement.…”
Section: Introductionmentioning
confidence: 99%
“…This claim is not empirically supported by the limited number of studies that extend their scope to non-participants; that is, the broader public. Among this emerging body of research, a key finding is that minipublics can help to foster favourable attitudes towards the political system, even among those who do not themselves participate (Boulianne 2018;Knobloch et al 2020). However, while these studies make a helpful contribution to our understanding of the democracyenhancing function that minipublics serve, they do not provide a clear answer to a crucial question that is pertinent to Lafont's critique: why would non-participants trust minipublics and the outcomes recommended by their participants?…”
Section: Introductionmentioning
confidence: 99%